2005
DOI: 10.1007/s10620-005-1598-9
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatoprotective Effect of Hepatic Stimulator Substance (HSS) Against Liver Regeneration Arrest Induced by Acute Ethanol Intoxication

Abstract: Male Wistar rats were randomized to receive ethanol (2.5 ml/kg by gastric intubation every 8 hr; group I), equal volumes of isocaloric to ethanol sucrose solution (group II), or ethanol and HSS (100 mg/kg intraperitoneally 10 and 16 hr after partial hepatectomy; groups III and IV, respectively) for up to 96 hr after partial hepatectomy, with ethanol administration starting 1 hr prior to partial hepatectomy. Animals were killed at 8, 12, 16, 20, 24, 28, 32, 36, 40, 44, 48, 60, and 96 hr after partial hepatectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Indeed, ALR has been shown to function as a survival factor for hepatocytes and depletion of ALR protein by antisense oligonucleotide leads to hepatocyte cell death [29]. Acute liver damage induced by toxins, such as ethanol, is known to stimulate hepatic stimulatory substance (HSS) activity in the injured livers, and exogenous HSS administration increased the injured liver hepatic proliferation post toxin treatment [30], [31]. ALR is a purified protein of HSS [1] and has been reported to stimulate hepatocyte proliferation directly as well as indirectly through Kupffer cells [3], [32].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, ALR has been shown to function as a survival factor for hepatocytes and depletion of ALR protein by antisense oligonucleotide leads to hepatocyte cell death [29]. Acute liver damage induced by toxins, such as ethanol, is known to stimulate hepatic stimulatory substance (HSS) activity in the injured livers, and exogenous HSS administration increased the injured liver hepatic proliferation post toxin treatment [30], [31]. ALR is a purified protein of HSS [1] and has been reported to stimulate hepatocyte proliferation directly as well as indirectly through Kupffer cells [3], [32].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that acute ethanol exposure will impair hepatic regeneration if administered 1 h before or 1 h after PHx surgery in rodents (19,44). However, such a protocol is complicated by the direct and indirect effects of ethanol and/or its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of microtubule formation has significant implications for mitosis, as well as intracellular trafficking, likely contributing to mitotic arrest at the metaphase/anaphase transition, formation of the mitochondrial permeability transition pore, and the subsequent initiation of apoptotic signaling involving the upregulation of pro-apoptotic Bcl-2 family proteins such as Bax/Bad/Bim and subsequent caspase activation (Bhalla, 2003; Giacca, 2005). This is likely a critical aspect of both hepatic injury associated with chronic ethanol exposure (e.g., Kondili et al, 2005) and ethanol-associated abnormalities in fetal brain and craniofacial development (e.g. Sulik et al, 1988).…”
Section: Discussionmentioning
confidence: 99%